Efforts to Prevent the Use of Addictive Substances of Students of SMA Wijaya Kusuma Mandiri - Suwarsit, Suwarsit; Sulastri, Sulastri; Setiyawati, Marina Ery (Abdi Masyarakat, 2024)
This research aims to prevent the use of addictive substances of SMA Wijaya Kusuma Mandiri students which is done by means of socialisation of legal analysis material on addictive substances in Indonesia challenges and solutions as well as anti-drug awareness for the younger generation as a form of State defence. The implementation of socialisation was carried out by lecturers from the National Development University Veteran Jakarta which was held on 06 November 2024. The results showed that Wijaya Kusuma Mandiri High School students not only gained an in-depth understanding of the dangers of using addictive substances but also knowledge of opportunities to continue their studies at state universities at Universitas Pembangunan Nasional Veteran Jakarta, especially non-academic achievements.